O projeto para o pavilhão brasileiro na expo' 92 em sevilha e a chamada arquitetura paulista - Fiorin, Evandro [UNESP] (2012)
This article discusses the controversy surrounding the winning project of the competition organized by the Brazilian Ministry of Foreign Affairs for the Brazilian pavilion at the Expo'92 in Seville, Spain; the views of architecture critics made at the time of the results, and, their implications for Brazilian architecture. At the beginning of the 90s, this competition was a kind of confrontation of ideas, between the architects who were in favour of a renewal of architecture and those who defended the resumption of national architectural traditions, buildings with large spans, constructed in reinforced concrete. These architects were the heirs of the so called Paulista architecture, which was characterised by the work undertaken from the 60's by important architects such as Vilanova Artigas and Paulo Mendes da Rocha. The modern references adopted by the winning project, from the architects Angelo Bucci, Alvaro Puntoni and José Oswaldo Vilela, sparked controversies because of the difficulty of resuming the teachings of the old modern masters when faced with new times. These controversies were related to the end of the military dictatorship in Brazil and the process of opening markets, and by the relevance of a re-evaluation of the so-called Paulista architecture.